Ruthenian denominational schools in Ruski Krstur and Kucura serve to preserve the language, culture, and identity of the Ruthenians in Vojvodina - Kwoka, Tomasz (Poznańskie Studia Slawistyczne, 2024)
Using the example of two Ruthenian denominational schools in Ruski Krstur and Kucura, the article presents the history of Ruthenian education in Vojvodina in the 18th and 19th centuries. The described institutions played an important role in preserving the language, culture, and identity of the small Ruthenian diaspora, which formed in Bačka and Srem from the mid-18th century. By outlining the history of Ruthenian education, particular emphasis is placed on the years around the turn of the 19th and 20th centuries, when, like other non-Hungarian national minorities, the Ruthenians were subjected to the process of Magyarization. The article also presents the profiles of the most famous teachers and graduates of Ruthenian schools, who played a key role in the cultural and national revival of the Ruthenians in Vojvodina in the first half of the 20th century.